PUBLIC RELATIONS COMMUNICATION STRATEGY IN STRENGTHENING EDUCATIONAL COLLABORATION IN THE PLANTATION SECTOR: EXPERIENCE OF COMMUNITY SERVICE IN THE DIRECTORATE GENERAL OF PLANTATIONS - Dafenta, Hadi; Rahmawati, Ima; Lestari, Hana (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
This community service program was carried out by Institut Agama Islam Sahid Bogor in collaboration with the Directorate General of Plantations, aiming to strengthen educational cooperation in the plantation sector through the implementation of effective public relations communication strategies. Using a participatory approach, the program involved a needs analysis and the design of communication strategies based on two-way communication principles and mutually beneficial relationship management. The findings revealed a communication gap between the Directorate General of Plantations and educational institutions, which hindered the development of a workforce aligned with the needs of the plantation industry. The implementation of dialogical and inclusive communication strategies proved to improve coordination and the overall effectiveness of collaboration among stakeholders. This initiative highlights the crucial role of public relations communication strategies in building sustainable synergy and offers a model for developing stronger cooperation between educational institutions and the plantation industry in Indonesia.